Perceptions and land law influences: unravelling colonial land law and forest management policies during British Malaya era - Md Sairi, Md Damiri; Hassan Zaki, Pakhriazad; Ismail, Mohd Hasmadi (Human Resource Management Academic Research Society, 2023)
This study explores the discrepancies in interpretations of land rules between state and federal levels, particularly concerning the recognition and definition of British law in land ownership, disposal, and acquisition. The objectives include analysing perceptions of colonial land law and forest management policy during the British Malaya era and comparing perception agreements regarding the influence of land law on administration and forest management policy. The study was conducted in Penang, Kelantan, and Perak using a structured questionnaire and a two-stage sampling procedure. Results show that a majority (more than 55%) agreed that British-Malaya land administration still influences present-day practices. Additionally, 79% agreed that the "National Land Code" was based on the Federated Malay State Land Code of 1926. Respondents disagreed with statements on colonial forest management policy but agreed (78.8%) with those regarding forest land administration influenced by the British era. The study suggests that land administration practices in the Federated Malay States served as models for subsequent British advisors. However, variations in perception pose challenges in collectively managing land laws related to forestry, necessitating a strong understanding between the public and stakeholders for effective forest-land decision-making and sustainable land development.